Nilai-Nilai Religi dalam Tradisi Beumao Dayak Ketunggau Sesaet (Sebuah Tinjauan Filosofis Budaya) - Ajung, Florensius (Universitas Tanjungpura, 2023)
This research was conducted to explore the religious values contained in the tradition of beumao Dayak Ketunggau Sesaet (heretic). The exploration of these values aims to provide information and make the Dayak Ketunggau Sesaet people aware of the importance of establishing a good relationship with God and the universe. The focus of this research is the Dayak Ketungau Sesaet tribe in Sekadau Hilir District, specifically in Selalong Village. The research method used by the author is qualitative, namely by conducting observations, interviews, and documentation. In the process of this research, the writer found out how rich the religious values contained in the tradition of beumao Dayak Ketunggau Sesaet are. The values contained in it are only focused on the relationship between humans, God, and the universe. This research aims to instill awareness and knowledge of the Ketunggau Sesaet Dayak people, especially young people so that they know how rich the cultural values are in the Ketunggau Sesaet Dayak tribe, and in the end, they also continue, revive and preserve their own culture, so what is there should not sink and die in the flow of changing times.